Acidic media enables oxygen-tolerant electrosynthesis of multicarbon products from simulated flue gas - Wang, Meng; Wang, Bingqing; Zhang, Jiguang; Xi, Shibo; Ling, Ning; Mi, Ziyu; Yang, Qin; Zhang, Mingsheng; Leow, Wan Ru; Zhang, Jia; Lum, Yanwei (Nature communications, 2024)
Renewable electricity powered electrochemical CO 2 reduction (CO 2 R) offers a valuable method to close the carbon cycle and reduce our overreliance on fossil fuels. However, high purity CO 2 is usually required as feedstock, which potentially decreases the feasibility and economic viability of the process. Direct conversion of flue gas is an attractive option but is challenging due to the low CO 2 concentration and the presence of O 2 impurities. As a result, up to 99% of the applied current can be lost towards the undesired oxygen reduction reaction (ORR). Here, we show that acidic electrolyte can significantly suppress ORR on Cu, enabling generation of multicarbon products from simulated flue gas. Using a composite Cu and carbon supported single-atom Ni tandem electrocatalyst, we achieved a multicarbon Faradaic efficiency of 46.5% at 200 mA cm -2 , which is ~20 times higher than bare Cu under alkaline conditions. We also demonstrate stable performance for 24 h with a multicarbon product full-cell energy efficiency of 14.6%. Strikingly, this result is comparable to previously reported acidic CO 2 R systems using pure CO 2 . Our findings demonstrate a potential pathway towards designing efficient electrolyzers for direct conversion of flue gas to value-added chemicals and fuels. Direct electroreduction of dilute CO 2 in flue gas streams is challenging due to the presence of O 2 impurities. Here the authors demonstrate that an acidic electrolyte can overcome this challenge, enabling the generation of multicarbon products from simulated flue gas at reasonable rates.